Archaic thought and sophistry in herodotus’ histories 3.38.1 : some remarks on the concept of νομος - Barrionuevo, Sergio Javier (2017)
Fil: Barrionuevo, Sergio Javier. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina.